2017
DOI: 10.1002/14651858.cd002021.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Opioid antagonists with minimal sedation for opioid withdrawal

Abstract: The evidence is current to December 2016. Study characteristicsWe identified 10 studies, including six randomised controlled trials (where people are randomly put into one of two or more treatment groups) and four prospective cohort studies (where participants could choose which treatment they received) involving 955 opioiddependent participants. Four of the studies took place in the UK, three in the USA, two in Italy and one in Australia. Nine of the 10 studies compared treatment with an opioid antagonist (na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 86 publications
0
6
0
2
Order By: Relevance
“…Lofexidine provides substantially more symptom relief than placebo; however, the comparative efficacy of lofexidine in combination with long-acting opioid agonists or opioid antagonists is still being characterized. 71 , 98–100 …”
Section: Cannabis During Acute Opioid Withdrawalmentioning
confidence: 99%
“…Lofexidine provides substantially more symptom relief than placebo; however, the comparative efficacy of lofexidine in combination with long-acting opioid agonists or opioid antagonists is still being characterized. 71 , 98–100 …”
Section: Cannabis During Acute Opioid Withdrawalmentioning
confidence: 99%
“…The efficacy of methadone or buprenorphine is comparable with low rates of adverse effects. 43,44 An important consideration when prescribing buprenorphine is the potential for precipitated withdrawal, a syndrome of worsening withdrawal symptoms when buprenorphine, a partial opioid agonist with high affinity for the opioid receptor, is administered when a full opioid agonist is also systemically present. To avoid this, buprenorphine should not be administered until at least 12 hours after the last dose of a short-acting opioid and up to 48 hours after the last dose of a long-acting opioid.…”
Section: The Addiction Consultmentioning
confidence: 99%
“…In situations when methadone is not available, the conversion of methadone to any opioid can be performed; however, the conversion calculations may not be bidirectional due to the long half-life of methadone ( 21 ). A multimodal approach ( 16 , 27 ) including the perioperative infusion of ketamine ( 28 , 29 , 30 ), clonidine ( 31 ), and the use of regional anesthesia ( 32 ) should be considered. In a retrospective cohort study performed by Macintyre et al ( 26 ), methadone opioid substitution therapy was continued and it showed the efficacy and safety of PCA opioids for the management of postoperative pain ( 26 ).…”
Section: Summary Of Evidencementioning
confidence: 99%